(untitled) (Academicia Globe: Inderscience Research, 2022)
The present review was carried out to show the importance of the biocontrol strategy in the control of plant pathogens, such as bacteria, fungi, and plant pests. Some microbial agents function in the increase of plant immunity by releasing some chemicals, such as antibiotic-like substances, secondary metabolites, which encourage positive defensive lines of the host plant against different pathogens. The review shows the importance of biological control in the management of plant pathogens, and that microbial-based beneficial agents are critical in this process, which provide the host with important roles to potentiate the host plants with some microbial bioactive metabolites that may increase the defense mechanisms against plant pathogens.